The effects of stress and self-esteem on life satisfaction of high school students: The moderated mediation model of growth mindset - Ju, Sun Mi; Kim, Suk Gyeong; Kim, Yeon Sun; LeE, Chang Seek (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to examine whether growth mindset moderates the mediation effect, when self-esteem mediates between stress and life satisfaction for high school students.Methods/Statistical analysis: In this study, SPSS win. 25.0 and PROCESS macro for SPSS version 3.4 were used for frequency, reliability, correlation, and moderated mediation effect analysis.Findings: First, it was noted that stress had significantly negative correlation with self-esteem and life satisfaction, but not with growth mindset. Second, as the result of moderated mediation effect analysis, the growth mindset had significant conditional indirect effects on the path to stress, self-esteem and life satisfaction. Thus, it is discovered that the mindset for growth moderated the path of relationships among stress, self-esteem and life satisfaction.Improvements/Applications: This result suggested mitigation measures through growth mindset in situations where stress adversely affects quality of life for high school students in Korea.